PENGARUH MEDIA PAPAN PINTAR TERHADAP KEMAMPUAN KOGNITIF ANAK DI RA AL-QODIR TAMAN SIDOARJO - Ratna Pangastuti; Yatimatul Huryanah; Nurul Qomaria; Siti Rahmah; Woro Susanti (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2020)
Potential development in inclusive children is done by means of group learning methods and classroom teachers and supervisors who use their respective strategies according to the needs of students. The problems examined in this study are (1) The form of learning in the classroom in the development of the potential of inclusive children (2) Inhibiting factors in developing the potential of an inclusive child (3) The results of the teacher in developing the potential of an inclusive child. This type of research is a type of descriptive qualitative research that took place in TK Nurul Huda, Karangasem Bali Regency. Data collection is done by conducting observations, interviews, and documentation. Data analysis is carried out by giving meaning to the data that was collected, then from that meaning conclusions are drawn. Checking the validity of the data is done by triangulation. The results showed (1) The form of learning conducted at TK Nurul Huda was a form of group learning, by uniting regular students with inclusive students (ABK) under the supervision of class teachers and special assistant teachers. (2) Inhibiting factors in developing the potential of inclusive children is inadequate facilities and infrastructure, lack of special assistant teachers. (3) The results of the development of the potential of inclusive children are quite good and proud of the principal, teachers, and student’s parents.